Primary immune‐mediated thrombocytopenia and immune‐mediated neutropenia suspected in a 21‐week‐old Maine Coon cat. Issue 7 (July 2014) - Best, MP; Fry, DR
<x xml:space="preserve">Abstract</x> Case report A 21‐week‐old Maine Coon cat presented with an acute‐onset coagulopathy. Severe concurrent thrombocytopenia and neutropenia were identified on peripheral blood smears and bone marrow cytology supported a peripheral consumptive process. Other than mild superficial haemorrhage, the cat was clinically well and screening for retroviral diseases, abdominal ultrasound examination, thoracic radiography, haematology and biochemistry panels did not identify an underlying disease. There was no historical pharmaceutical or toxicological trigger noted and the cat was from an area without endemic Ehrlichia spp. There was a rapid resolution of both cytopenias following treatment with immunosuppressive doses of prednisolone, though a mild relapse occurred during gradual prednisolone withdrawal and was responsive to a dose increase. Conclusions This report describes this combination of diseases for the first time in a cat and presents a younger patient than previously described with feline primary immune‐mediated haematological disease.